Biotypes of Cândida albicans isolates from aids patients - Silva, Maria do Rosário Rodrigues; Fernandes, Orionalda de Fátima L.; Costa, Márcio Rodrigues; Costa, Théo Rodrigues; Silva, Simonne A.; Gambale, Walderez; Paula, Claudete Rodrigues (Revista de Patologia Tropical / Journal of Tropical Pathology, 2011)
The phenotypic features of C. albicans oral isolates recovered from AIDS patients were determined by serotyping, morphotyping and biotyping in nine media with different biochemical charaeterístics. The patients were divided into: Group l, comprising subjects with detectable lesions of lhe oral mucosa and Group 2, corresponding to carrier patients. Despite observing a greater frequency of serotype B isolates among subjects with symptomatic oral candidosis as compared to lhe other group of patients, these results were not statistically significam. When correlating lhe presence of serotypes A and B with T lymphocyte counts, we verified thal occurrence of serotype B was more prevalent (p<0.05) than serotype A in individuais with CD4"" T < 200 cells/mm3. The occurrence of fringes greater than 3 mm in length was a typical feature of the oral isolates from our AIDS patients, though no differences in this respect were detected between the two groups of subjects. A lack of ability to assimilate urea and sorbose and variation in sensibility to 5-fluorocytosine were also features expressed by the majority of the isolates, with a predominance of the biotype 347 in 51.9% of ali the oral isolates studied.